MONITORING OF WATER POLLUTION IN HOT CLIMATES - Guzal T. Iskandarova; Aziza M.Yusupxo’jaeva (Central Asian Journal of Medicine, 2022)
It has long been noticed the tendency of mankind to hang catchy labels on everything that comes to hand, especially on any epoch-making events. So the twentieth century, which has sunk into the past, was called - oil and nylon, nuclear and space, information and computer. The coming age from its very threshold is often called the water age, and inveterate pessimists do - the age of water wars. Meanwhile, scientists have long calculated that approximately 1366 million cubic kilometers of water have accumulated on our small planet, or more than two hundred million tons per average earthling. But for a completely comfortable existence, hundreds of tons of water per year are more than enough for an earthling, if we focus on reasonable standards for domestic water supply. And each of these tons, obeying the inexorable world cycle, sooner or later returns to the bosom of nature, so why sound the alarm? However, there is more than enough reason for concern. 97.5% of the planet’s water resources located in the seas, oceans and depths of the earth are not yet suitable for consumption due to excessive mineralization.